Crònica legislativa de Catalunya. Segon semestre de 2022. “Un període caracteritzat per les primeres derivades judicials i polítiques del nou marc legal sobre l’ús i l’aprenentatge de les llengües oficials en l’ensenyament no universitari” - Ridao i Martín, Joan (Revista de llengua i dret, 2023)
The Legislative Chronicle of the second semester of 2022 echoes, as is usual, the rules that affect the uses, rights and legal regime of the Catalan and Aranese languages during this period. It is, in any case, a small number of provisions related to the activity of promoting linguistic standardization or to the personnel selection processes in which linguistic requirements have an impact. Much more relevant, however, is the analysis of the consequences derived from the new educational linguistic framework, specifically the position adopted by the TSJC, the return of the issue to the Constitutional Court and the intergovernmental agreement adopted on this particular within the framework of the so-called table of the Generalitat-State dialogue.